Fatigue laws for Brazilians asphalt rubber mixtures obtained in 4 point bending tests - Fontes, Liseane P. T. L. (2009)
The majority of Brazilian roadpavements consistsof thin pavement structures unable to resist the damage caused by heavy loads and an increasing traffic demand. The main structural distress modes found in Brazilians asphalt layers is fatigue cracking. One of the prom-ising techniques to improve the pavement performance is through asphalt rubber mixtures, which make use of crumb rubber from scrap tires to modify and enhance the properties of the asphalt. The inexistence of fatigue laws for asphalt rubber mixtures to be applied in road design encouraged the study presented in this paper, aiming at the development of prediction models for fatigue and dynamic modulus from the results obtained in laboratory tests. Four mixtures (gap and dense graded) containing Brazilian terminal blend asphalt rubbers were assessed through four point bending tests to evaluate their fatigue and stiffness properties.